PTH-113 The success of kaffes stent insertions for post liver transplant anastomotic strictures. (8th June 2018) - Joshi, Deepak; Warner, Ben; Harrison, Phillip; Devlin, John; Reffitt, David; El-Sherif, Yasser; Khorsandi, Shirin; Prachalias, Andreas; Cerisuelo, Miriam Cortes; Menon, Krishna; Jassem, Wayel; Srinivasan, Parthi; et al.
Abstract : Introduction: Biliary anastomotic strictures (AS) occur in around 30% of patients following liver transplantation and are treated by endoscopic dilatation and plastic stent (PS) insertion. However, AS frequently recur and patients require multiple procedures. The Kaffes stent (KS, Taewoong Medical) is a removable, covered metal stent designed to be deployed across AS. Methods: To examine outcomes in patients with AS, we compared a recent cohort of patients treated using KS with a historical cohort of patients who received PS. Results: The 22 patients (12 females) treated by KS had mean age 55 (range 22–69) years; 11 patients had DBD and 11 DCD grafts; mean cold ischaemia time was 9.6±3.3 hours. Four patients had failed previous treatment with PS. To date, 16 patients have had KS removed. The 69 patients (20 female) treated by PS were similar, mean age 51 (range 28–79) years; 47 patients had DBD and 22 DCD grafts; mean cold ischaemia time was 8.9±3.1 hours. AS resolved after one deployment of KS in 14 out of 16 patients (88%) compared to 26 out of 69 patients (38%) receiving their first PS (Relative Risk of persistent stricture (KS vs PS)=0.2, 95% CI 0.05–0.74; p=0.016; number to treat by KS for one benefit=2, 95% CI 1.3–4.0). There were no complications, including stent migration, after KS compared to 6 (8.4%) in the PS group (3 cholangitis, 2 pancreatitis, and 1 bleeding). All KS were removed successfully, although 1 stent needed 2 attempts because of wire migration. Following initial ERCP, PS patients required more ERCPs (mean 2.71 vs 1.13 more; p<0.01) and 32% required biliary reconstruction. Conclusion: Our data indicate that the KS is a promising Method for managing post-transplant AS because the majority of strictures are treated by deployment of a single stent at first ERCP.